Water and sediment quality assessment at São Lourenço River-SP - Angélica Megda da Silva; Denis Moledo de Souza Abessa; Paulo Augusto Zantune Pamplin; Maria Beatriz Bohrer-Morel (O Mundo da Saúde)
São Lourenço River (SLR) is part one of the Ribeira de Iguape River basin, and provides water to supply the cities of São Lourenço da Serra and Juquitiba. The SLR also receives large amounts of pollution from these municipalities. In this context, this study aimed to evaluate the impacts of the release of residues from water treatment (WTP) and wastewater treatment plants (WWTP) on the sediments of the SLR. Six sampling stations were established along the river (including upstream and downstream of both WTP and WWTP), and 6 sampling campaigns for sediments were conducted. In such 6 surveys sediments were collected for ecotoxicological tests, in 2 surveys, material was also collected for benthic community evaluation (March and September 2006), and in one survey samples for chemistry were taken (September 2006). Seven campaigns were conducted for water sampling aiming to ecotoxicological tests. The metal levels were low for all samples. Ecotoxicological tests with sediments showed acute toxicity in samples collected downstream to both WTP and WWTP in November 2005 and March 2006, and chronic effects for all samples in November 2005 and September 2006. All samples from SLS 008 were toxic. Results showed negative responses in the benthic community, with low richness and diversity. The water samples collected downstream to WTP presented acute ecotoxicity in 2004 and 2006. No chronic toxicity was observed for waters. The results indicate that SLR is influenced by other anthropic activities, beyond to WTP and WWTP discharges, and that sediments are more affected in this ecosystem.